Studies on Schismatoglottideae (Araceae) of Borneo IX: a new genus, Hestia, and resurrection of Apoballis. - Wong, Sin Yeng; Boyce, P.C (SpringerOpen Journal, 2010)
Hestia S.Y. Wong & P.C. Boyce is described as a new genus from Sarawak typified by Hestia longifolia (Ridl.) S.Y. Wong & P.C. Boyce (syn. Schismatoglottis longifolia Ridl.), and based on combined molecular and morphological analyses the genus Apoballis Schott is resurrected. A key to the Schismatoglottideae sensu Wong & Boyce is presented, and Hestia is illustrated.